2017
DOI: 10.4049/jimmunol.1600506
|View full text |Cite
|
Sign up to set email alerts
|

IL-35 Suppresses Lipopolysaccharide-Induced Airway Eosinophilia in EBI3-Deficient Mice

Abstract: EBI3 functions as the subunit of immune-regulatory cytokines, such as IL-27 and IL-35, by pairing with p28 and p35, respectively. We treated wild-type and EBI3-deficient mice with intratracheal administration of LPS and obtained bronchoalveolar lavage fluid (BALF) 24 h later. Although neutrophils were the predominant cells in BALF from both groups of mice, eosinophils were highly enriched and there was increased production of eosinophil-attracting chemokines CCL11 and CCL24 in BALF of EBI3-deficient mice. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
6
21
0
Order By: Relevance
“…On the other hand, airway delivery of anti-IL35 significantly increased the number of eosinophils in the BALF from LPS-stimulated WT mice. This study demonstrated that IL-35 inhibits LPS-induced airway eosinophilia, at least in part by reducing the local production of CCL11 and CCL24 [28]. In our study, there was a significant increase in IL-35 level in the sputum of patients with NA.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…On the other hand, airway delivery of anti-IL35 significantly increased the number of eosinophils in the BALF from LPS-stimulated WT mice. This study demonstrated that IL-35 inhibits LPS-induced airway eosinophilia, at least in part by reducing the local production of CCL11 and CCL24 [28]. In our study, there was a significant increase in IL-35 level in the sputum of patients with NA.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, there was a negative correlation between IL-35 and FEV1%, FeNO and a positive correlation between IL-35 and the number of neutrophils and IL-1-related (IL-1β, 6, and 8) inflammatory mediators. These findings suggest that IL-35 may play a key role in the infiltration and activity of eosinophils [28] and neutrophils [29] in asthma and may participate in the airway inflammation mechanism of asthma phenotypes. The function of IL-35 is complex and the results of different studies may be contradictory.…”
Section: Discussionmentioning
confidence: 81%
“…Mice C57BL/6 mice were purchased from Japan SLC (Hamamatsu, Japan). IL-27-deficient mice (WSX1 -/and p28 -/mice) were described previously (11,41,42). Mice were housed and bred in a specific pathogen-free facility at Kindai University Faculty of Medicine and Tottori University Faculty of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Increased eosinophils could be pathogenic in various diseases, such as eosinophilic pneumonias, allergic asthma, and eosinophil‐associated gastrointestinal disorders . Recent findings suggest that IL‐35 decreases airway eosinophilia by reducing the production of the eosinophil‐attracting chemokines CCL11 and CCL24, which demonstrates that IL‐35 may provide a new therapeutic strategy to reduce tissue recruitment of eosinophils in such diseases . In addition, studies have shown that the expression of IL‐35 is down‐regulated in chronic obstructive pulmonary disease, a chronic bronchitis and emphysema characterized by airflow obstruction .…”
Section: Il‐35 and Immune‐related Diseasesmentioning
confidence: 99%
“…65,66 Recent findings suggest that IL-35 decreases airway eosinophilia by reducing the production of the eosinophil-attracting chemokines CCL11 and CCL24, which demonstrates that IL-35 may provide a new therapeutic strategy to reduce tissue recruitment of eosinophils in such diseases. 67 In addition, studies have shown that the expression of IL-35 is down-regulated in chronic obstructive pulmonary disease, a chronic bronchitis and emphysema characterized by airflow obstruction. 68 Moreover, decreased IL-35 levels were negatively correlated with the smoking status, indicating that IL-35 can serve as a biomarker to estimate progression of chronic obstructive pulmonary disease.…”
Section: Il-35 and Allergic Airway Diseasementioning
confidence: 99%